2009
DOI: 10.1016/j.tourman.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Does gender affect media choice in travel information search? On the use of mobile Internet

Abstract: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 41 publications
3
81
0
3
Order By: Relevance
“…M a n u s c r i p t 16 Finally, our study also confirms the influence of gender and age in the online informationseeking profiles of travellers [18,68]. Males tend to prioritize satisfaction of information needs related to destination information (in terms of transportation and weather) through informal information sources; females also emphasise on transportation and weather travel information, but they do not attribute any core preference to a specific type of online information source.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…M a n u s c r i p t 16 Finally, our study also confirms the influence of gender and age in the online informationseeking profiles of travellers [18,68]. Males tend to prioritize satisfaction of information needs related to destination information (in terms of transportation and weather) through informal information sources; females also emphasise on transportation and weather travel information, but they do not attribute any core preference to a specific type of online information source.…”
supporting
confidence: 75%
“…In this process, several factors intervene, such as trust on the accumulated information from the online information source [15] and personal elements (e.g. age, gender and online information literacy capacities [16][17][18]), which impact the selection of information sources and the overall satisfaction of information needs. Extant tourism information-seeking studies have concluded that information search may be conceptualized as a series of interrelated activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the context of mobile internet usage, Okazaki and Hirose (2009) found significant differences between males and females in terms of their satisfaction from, ATT toward and habitual use of the mobile internet, suggesting that female respondents gave higher importance to these constructs in the mobile internet context. Finally, Morris et al (2005) did not find any significant gender differences in the determinants of technology use.…”
Section: Moderating Effect Of Gender On Adoption Intentionmentioning
confidence: 57%
“…A considerable number of studies (e.g., Dong and Zhang, 2011) have reported that gender influences consumers' perceptions of the adoption of information technology. Some of these studies have examined the moderating effects of gender on the adoption and the usage of innovative IS including m-banking (Riquelme and Rios, 2010), m-commerce (Faqih and Jaradat, 2015), and the mobile internet (Okazaki and Hirose, 2009), and the impact of gender differences on adopting new technologies has been recognized as an important factor by academics and practitioners alike (Faqih and Jaradat, 2015). Riquelme and Rios (2010) examined gender as a moderating variable in m-banking services adoption and concluded that ease of use has a stronger influence on female respondents than male respondents, whereas relative advantage has a stronger effect on the perception of usefulness by male respondents.…”
Section: Gendermentioning
confidence: 99%
“…In addition to this, the development of mobile Internet networks, low cost and the extensive availability of wireless Internet are other factors causing an increase in mobile Internet usage. Moreover, various applications (known as "apps") on smartphones enable people to stay online longer and use smartphones excessively (Okazaki & Hirose, 2009). There is a common sense among scholars that there exists a strong relation between the nomophobia levels of the younger generation and mobile Internet usage due to the inevitable combination of smartphones and the Internet (Anshari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%